Contemporary Management of Benign and Malignant Parotid Tumors - Thielker, Jovanna; Grosheva, Maria; Ihrler, Stephan; Wittig, Andrea; Guntinas-Lichius, Orlando (Frontiers in Surgery, 2018)
Background: To report the standard of care, interesting new findings and controversies about the treatment of parotid tumors. Methods: Relevant and actual studies were searched in PubMed and reviewed for diagnostics, treatment and outcome of both benign and malignant tumors. Results: Prospective trials are lacking due to rarity of the disease and high variety of tumor subtypes. Conclusion: The establishment of reliable non-invasive diagnostics tools for the differentiation between benign and malignant tumors is desirable. Prospective studies clarifying the association between different surgical techniques for benign parotid tumors and morbidity are needed. The role of adjuvant or definitive radiotherapy in securing loco-regional control and improving survival in malignant disease is established. Prospective clinical trials addressing the role of chemotherapy/molecular targeted therapy for parotid cancer are needed. An international consensus on the classification of parotid surgery techniques would facilitate the comparison of different trials. Such efforts should lead into a clinical guideline.